2007
DOI: 10.1523/jneurosci.4799-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Coupling of Neuronal Nitric Oxide Synthase Phosphorylation to the NMDA Receptor Regulates AMPA Receptor Trafficking and Neuronal Cell Death

Abstract: Postsynaptic nitric oxide (NO) production affects synaptic plasticity and neuronal cell death. Ca 2ϩ fluxes through the NMDA receptor (NMDAR) stimulate the production of NO by neuronal nitric oxide synthase (nNOS). However, the mechanisms by which nNOS activity is regulated are poorly understood. We evaluated the effect of neuronal stimulation with glutamate on the phosphorylation of nNOS. We show that, in cortical neurons, a low glutamate concentration (30 M) induces rapid and transient NMDAR-dependent phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 67 publications
(78 reference statements)
7
133
1
5
Order By: Relevance
“…7, 23). The CaMKII-mediated regulation of nNOS cannot explain this effect, as CaMKII inhibits rather than activates nNOS (40,43,44). By contrast, the NO-induced CaMKII autonomy indicates that nNOS is instead upstream of CaMKII in excitotoxic death signaling.…”
Section: Discussionmentioning
confidence: 99%
“…7, 23). The CaMKII-mediated regulation of nNOS cannot explain this effect, as CaMKII inhibits rather than activates nNOS (40,43,44). By contrast, the NO-induced CaMKII autonomy indicates that nNOS is instead upstream of CaMKII in excitotoxic death signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings establish that PKA also directly phosphorylates and activates nNOS-S1412 in a physiologically meaningful way similar to endothelial PKA phosphorylation of eNOS-S1177 (37). Rameau et al (17,21) used immunofluorescent staining techniques to show that NMDA stimulation of cortical neuronal cultures enhances phosphorylation of nNOS at S1412 in specific and localized synaptic signaling. Conceivably, Akt and PKA phosphorylation of nNOS interact in a regulated fashion.…”
Section: Phospho-protein / Total Proteinmentioning
confidence: 99%
“…nNOS possesses a phosphorylation consensus sequence at S1412 that closely resembles the sequence surrounding eNOS-S1179, and is thought to be a target for Akt in some systems (15)(16)(17)(18)(19)(20)(21). We wondered whether nNOS phosphorylation at S1412 might regulate penile erection.…”
mentioning
confidence: 99%
“…47 We previously demonstrated that neuronal-derived NO increased phospho-CREB in cultured retinal cells in an ERK-dependent manner. 23 On the other hand, nNOS activity has been associated with both glutamate-induced excitotoxicity in cortical neurons 48 and AMPA-induced apoptosis in the retina. 15 We showed that calcium influx, nNOS activity and NO production were high in E6 when compared with E8 retinas.…”
Section: Discussionmentioning
confidence: 99%